hi fellas, i need a very silly help for my work. i have this equation as r=r(p)

r=p+0.645*(4*pi)^(-3/4)*p^(3/4)

or, simply r=p+ap^(3/4), where a is a constant..

what i need is an expression of my equation as p=p(r)..

i want this whole term in respect of p now, this might be very silly but i don't get the exact curve in the graph when i m putting it using some logarithmic result.. i deduced it to be

log p+(3/4)log p=log r-(3/4)log a.................and it might not be correct..

can you please help me ?